Probabilistic modelling of the stability of a pipeline on the sea-bed in intermediate waterdepth - Geustyn, Leon Casper (Stellenbosch : Stellenbosch University, 2012)
Thesis (Ph.D.) -- University of Stellenbosch, 1987.